Modeling the effect of air flow, impeller speed, frother dosages, and salt concentrations on the bubbles size using response surface methodology. (1st March 2019) - Arancibia-Bravo, María P.; Lucay, Freddy A.; López, Jean; Cisternas, Luís A.
Graphical abstract: Highlights: Response surface methodology was adopted to study bubble size. Air flow, impeller speed, frother and salt concentrations were used as factors. The significant factors were identified by using analysis of variance method. The resulting correlations were capable of predicting bubble sizes. Abstract: The size of bubbles plays an important role in the performance of a flotation system in mineral processing. The inorganic salt studied in this work, stabilizes the interfacial air-liquid films which inhibit bubble coalescence and therefore the bubble size. In this work, the response surface methodology (RSM) was adopted to study, at laboratory-scale tests, the influence of various process parameters such as air flow, impeller speed, frother dosages, and salt concentrations on the bubble size. The significance of these parameters was identified by using the analysis of variance (ANOVA). The resulting correlations were capable of predicting bubble sizes which were in excellent agreement with experimental data. Several saline solutions were used including a synthetic sea water solution, NaCl, KCl, and MgSO4 .